Analisis Kinerja Perusahaan Umum Daerah Air Minum Tirta Senentang - Mardonius, Emanuel; Nurhayati, Nurhayati (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
The demand for clean water will continue to increase along with the growth of the city's population with sufficient quality and quantity to ensure a better life. The provision of clean water in Sintang City is the responsibility of Tirta Senentang Municipal Waterworks, the leading supplier of clean water. This study aims to measure and analyze the performance of clean water services in Sintang City. The data used in this study are primary and secondary. Primary data is in the form of public perception. Namely, customers obtained through questionnaires. Secondary data were obtained from a literature review, Tirta Senentang Municipal Waterworks performance report, Sintang Regency in numbers, and other literature. This research was conducted by analyzing the performance of Tirta Senentang Municipal Waterworks based on normative aspects (service, operation, and human resources (HR)) and analysis of public perceptions (customers). The results showed that based on public (customer) perception, the performance of Tirta Senentang Municipal Waterworks was good. However, normatively, several things still need to be improved in the performance of Tirta Senentang Municipal Waterworks, especially the service aspect.